The Effect Of Reward And Punishment On The Performance of Employees of PT. Bengkulu Magic Marketing - Regy Yernandes; Melda Yunita (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of rewards and punishments on employee performance at PT. Marketing Sakti Bengkulu. This study used total sampling techniques with a sample size of 60 respondents. The results of the t-test and F-test showed that rewards and punishments both partially and simultaneously had a positive and significant effect on employee performance. The coefficient of determination obtained was 67.7%, indicating that 67.7% of employee performance was affected by rewards and punishments. The remaining 32.3% was affected by other factors not explained in this study.